Design And Analysis of Optical Line Terminal (OLT) And Optical Distribution Cabinet (ODC) Devices In The Fiber To The Home (FTTH) Network Trainer Module In The G316 Laboratory, Building G, State Polytechnic Of Padang - Fachri Adrian; Yulindon Yulindon (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This study aims to design and analyze the performance of Optical Line Terminal (OLT) and Optical Distribution Cabinet (ODC) devices in the Fiber to the Home (FTTH) network trainer module at the SKSO G316 Laboratory, Padang State Polytechnic. The research methods included design simulation using Optisystem software, physical implementation of the trainer module, and attenuation measurement using an Optical Power Meter (OPM). The results show that attenuation under normal core conditions (orange) is stable in the range of 14.94–16.23 dB, while core bending (green) and core damage (blue) conditions cause a significant increase in attenuation to 16.28 dB and 16.01 dB at a wavelength of 1310 nm. The length of the dropcore cable (10 m, 15 m, 20 m) showed an effect on the increase in attenuation with an additional attenuation increase of 0.9 dB per 5 meters. The simulation results and actual measurements are consistent with the link power budget calculations and meet the technical specifications with total attenuation below the maximum limit of -28 dB. This trainer module is useful as a learning medium for analyzing FTTH network performance and the impact of physical disturbances on optical fiber transmission.